Diastereoselective Synthesis of (3R,5R)-γ-Hydroxypiperazic Acid - Gerrein, Taylor A.; Elbatrawi, Yassin M.; Del Valle, Juan R. (Synlett, 2021)
We report an asymmetric synthesis of the (3R,5R)-γ-hydroxypiperazic acid (γ-OHPiz) residue encountered in several bioactive nonribosomal peptides. Our strategy relies on a diastereoselective enolate hydroxylation reaction and electrophilic N-amination to provide the acyclic γ-OHPiz precursor. This orthogonally protected α-hydrazino acid intermediate is amenable to late-stage diazinane ring formation following incorporation into a peptide chain. We determined the N-terminal amide rotamer propensity of the γ-OHPiz residue and showed that the γ-OH substituent enhances trans-amide bias relative to piperazic acid.
Keywords: nonribosomal peptides; natural products; piperazic acid; α-hydrazino acid; oxaziridine